(De) writing women in the canon of british postgraduate studies (2007)
Abstract: Lessons on literature written in English have tended to focus on male writers, being dominated by authors such as Shakespeare, Wordsworth, Coleridge or Joyce. Men govern literature syllabuses, or what is the same, the canon of English literature. Although universities are inhabited by numerous female students and professors, the writers dealt with still seem to be predominantly male. For this reason, the present paper intends to check empirically if this common assumption is true. To do so, it will focus on the postgraduate programmes offered by half the British universities’ English departments, taking into account two major parameters: the university type (ancient, red brick or new) and the period/subject the master deals with (Romanticism, the Victorian period, the 20th century and colonial, «national» and women’s literatures)